Hybrid of NiCo2S4 and nitrogen and sulphur-functionalized multiple graphene aerogel for application in supercapacitors and oxygen reduction with significant electrochemical synergy. (1st September 2016) - Tingting, Yang; Ruiyi, Li; Zaijun, Li; Zhiguo, Gu; Guangli, Wang; Junkang, Liu
Graphical abstract: The paper reported the construction of NiCo2 S4 /nitrogen and sulphur-functionalized multiple graphene aerogel (NiCo2 S4 /N, S-MGA). The introduction of nitrogen and sulphur-functionalized multiple graphene aerogel not only increase the structural stability of NiCo2 S4, but also improves the electron transfer and the electrolyte transport. Since the hybridization of NiCo2 S4 with nitrogen and sulphur-functionalized multiple graphene aerogel achieves a significantly electrochemical synergy, the hybrid electrode exhibits excellent electrochemical performance and may be widely applied in various high-capacitance supercapacitors. Highlights: The paper first reported the synthesis of NiCo2 S4 /N, S-GMA hybrid. The hybrid electrode provides an excellent electrochemical performance. The capacitance performance can be improved by increasing the GO gelation cycle. The hybrid of NiCo2 S4 and N, S-GMA achieves a significant electrochemical synergy. The hybrid/activate carbon supercapacitor has high energy density and power density Abstract: The paper reports a promising hybrid of NiCo2 S4 and nitrogen and sulphur-functionalized multiple graphene aerogel (N, S-MGA) for application in supercapacitors and oxygen reduction. The NiCo2 S4 /N, S-MGA was constructed by in-situ growth of ultrathin NiCo2 S4 nanoflakes on dense and strong graphene conductive network of N, S-MGA. The resulting composite displays a well-defined three-dimensional architecture with hierarchical porous structure. The unique architecture not only enhances the structural stability of NiCo2 S4 and effectively prevents the agglomeration of NiCo2 S4 flakes and graphene sheets, resulting in high specific surface area of 76.3 m 2 g −1, but also accelerates the electron transfer and electrolyte transport during the electrochemical process. The hybrid of N, S-MGA with NiCo2 S4 achieves to significant synergy in the electrochemical reaction. The oxygen reduction further improves the electrode reactions, leading to an enhanced capacitance (about 23%). The NiCo2 S4 /N, S-MGA electrode exhibits high specific capacitance (822.6 F g −1 at the current density of 1 A g −1 ) and good rate-capability (556.8 F g −1 at the current density of 10 A g −1 ) for supercapactors, and excellent catalytic activity for oxygen reduction reaction in an O2 -saturated 1.0 M KOH electrolyte using a three-electrode test system. The asymmetric supercapacitor of NiCo2 S4 /N, S-MGA/activated carbon provides the energy density of 122 W h kg −1 at the power density of 800 W kg −1 and 103.1 W h kg −1 at the power density of 3200 W kg −1 in a two-electrode test system in an O2 -saturated 1.0 M KOH electrolyte. The energy density is much higher than that of single NiCo2 S4 electrode and N, S-MGA electrode. Such a good capacitive performance make it can be used as the electrode materials for next-generation high-performance supercapacitors.